Plant oil-based shape memory polymer using acrylic monolith - T. Tsujimoto; E. Ohta; H. Uyama (eXPRESS Polymer Letters)
This article deals with the synthesis of a plant oil-based material using acrylic monolith. An acrylic monolith bearing oxirane groups was prepared via simple technique that involved the dissolution of poly(glycidyl methacrylate-comethyl methacrylate) (PGMA) in ethanolic – aqueous solution by heating and subsequent cooling. The PGMA monolith had topologically porous structure, which was attributed to the phase separation of the polymer solution. The PGMA monolith was impregnated by epoxidized soybean oil (ESO) containing thermally-latent catalyst, and the subsequent curing produced a crosslinked material with relatively good transparency. The Young’s modulus and the tensile strength of polyESO/PGMA increased compared with the ESO homopolymer. The strain at break of polyESO/PGMA was larger than that of the ESO homopolymer and crosslinked PGMA. Furthermore, polyESO/PGMA exhibited good shape memory-recovery behavior.